1994
DOI: 10.1039/p29940001097
|View full text |Cite
|
Sign up to set email alerts
|

NMR and UV–VIS Investigation of water-soluble fullerene-60–γ-cyclodextrin complex

Abstract: Fullerene-60 can be made water-solu ble by forming an inclusion complex with y-cyclodextrin (y-CD). The complex between C , and y-CD is selectively formed; neither por R-CD, nor C, , takes part in complex formation. The UV-VIS and 13C NMR spectra of C , , in the complex are almost identical to those of C, , in organic solvents. The 'H NMR spectrum of the host, y-CD, in the complex has been identified. Only small differences to the spectrum of the free host are observed; this is interpreted as being due mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…2A), and these were distinct from those of free g-CDx and could be assigned to the C 60 Ág-CDx complex. 10 In the same manner, new peaks assigned to the 2Ág-CDx and 3Ág-CDx complexes appeared in the respective spectra ( Fig. 2B and C), which indicates that 2 and 3 are solubilised in water by inclusion in g-CDx.…”
mentioning
confidence: 73%
“…2A), and these were distinct from those of free g-CDx and could be assigned to the C 60 Ág-CDx complex. 10 In the same manner, new peaks assigned to the 2Ág-CDx and 3Ág-CDx complexes appeared in the respective spectra ( Fig. 2B and C), which indicates that 2 and 3 are solubilised in water by inclusion in g-CDx.…”
mentioning
confidence: 73%
“…Several systems might coexist depending on the relative concentration of cyclodextrin and C 60 , the type of preparation, the time and temperature of storage, and the presence or exclusion of air [10,[27][28][29]. In agreement with previous studies, we confirmed that mainly two forms of complexes resulted between C 60 and c-CD: (i) one featuring the C 60 included in the cavities of two c-CD, the solution having a magenta colour, typical of non-aggregated C 60 , with the ground state absorption spectrum exhibiting a small, sharp and characteristic peak at 408 nm and (ii) a second form, partially consisting of non-inclusion complexes [30], where the C 60 molecules are associated in clusters surrounded by several c-CD [10,29], the solution being yellowish-brown, a typical colour of C 60 aggregates without the 408 nm peak in the absorption ground state spectrum. In all our investigations, we exclusively used the first type of complex.…”
Section: Ground State Absorption Spectra Of C-cd/c 60 Inclusion Complmentioning
confidence: 99%
“…These CD are also an interesting matrix for spectroscopic studies since they are transparent throughout a part of the IR, and in the visible and near-UV spectral region. The internal diameters of the largest CD, the c-CD which are constituted by 8 glucose units, allow the formation of 2:1 c-CD/[60]fullerene inclusion complexes (c-CD/C 60 ) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…γ-CD with a big cavity could encapsulate C60 and avoid aggregation [97]. The cell inhibition was dependent on the ability of ROS production (especially, 1 O2) and cellular uptake.…”
Section: Accepted Manuscriptmentioning
confidence: 99%